Redirecionamento de dexametasona e diclofenaco e efeito sinérgico com ácido nalidíxico, ciprofloxacino e vancomicina frente a Enterococcus spp. - Marion, Sara de Lima (2022)
The spread of multi-antibiotic resistant bacteria (MDR) has compromised the available therapeutic arsenal. Thus these MDR pathogens have become a public health problem resulting in high morbidity and mortality rates. As a way to encourage the search for new effective drugs, World Health Organization published a report showing the reduction of the discovery of new antibiotics. In it the pathogen vancomycin-resistant Enterococcus faecalis, common in hospital infections, was considered a high priority agent, urgently needing the development of new active drugs. Thus, the scientific community has been looking for strategies in the identification of new effective antibiotics. The repositioning of medicines has emerged as a promising alternative since it is considered as a process aimed at the reuse of drugs diseases other than that of origin of their indication. It has gained the attention of the scientific community for the advantages compared to the traditional method of developing active substances: reduction of time and costs in the process. Therefore, the present study aimed, through the manuscript, analyze the antibacterial activity of drugs anti-inflammatory dexamethasone and diclofenac and possible synergistic interaction with standard: nalidixic acid, ciprofloxacin and vancomycin against bacterial strains of clinical isolates of Enterococcus faecium and faecalis and American Type Culture Collection (ATCC) standard strains. To evaluate the antibacterial activity of the drugs, the minimum inhibitory concentration (MIC) was performed. The interaction with antibacterials was evaluated by the checkerboard method and the fractional inhibitory concentration index (FICI) was calculated to define synergism. When tested alone, dexamethasone presented MIC that varied in 512 and 1024 μg mL-1 compared to clinical isolates and ATCC strains. Diclofenac also obtained this variation, however for the two strains ATCC showed a MIC of 2048 μg mL-1. These drugs are candidates for redirection despite generally presenting higher MIC compared to antibiotics alone, when used in conjunction with each of the antibiotics, they presented relevant reductions in the MIC of both drugs together. Dexamethasone reduced the MIC by up to 2048 times when combined with any of the three antibiotics, diclofenac reduced the MIC by up to 2048 times if used in conjunction with vancomycin and up to 1024 times in combination with nalidyxic acid or ciprofloxacin. The concentration of MIC of nalidixic acid and vancomycin when used in combination with dexamethasone or diclofenac reduced its concentração of MIC by up to 64 times. When these drugs tests were used combined with ciprofloxacin, the concentration of the antibiotic was reduced by up to 128 times. Thus, the use of non-antibiotics with antimicrobials aiming at synergism is an alternative for the treatment of serious infections due to the advantages presented. However, further studies are still needed to elucidate the mechanisms of action of these drugs as well as in vivo studies.